Evaluation of a short-term medical mission to Syrian refugee camps in Turkey - Nora Alghothani (Thieme Medical and Scientific Publishers Pvt. Ltd., 2012)
Background: The escalating political and humanitarian crisis in Syria has left thousands detained, killed or displaced in neighboring countries. Given the permission and co-operation of the Turkish health authorities, a short-term medical mission to the Syrian refugee camps in the Hatay province was arranged. Materials and Methods : To assess this mission′s impact and potential expansion to serve other more emergently inflicted areas both inside and outside the Syrian borders, an evaluation was conducted via survey questionnaire of participating physicians. Results: While almost all respondents found the experience worthwhile and fulfilling, medical, social and educational challenges as well as possible solutions were outlined. Conclusion: The use of several specified principles to further guide efforts towards providing service, education, relief, and awareness would result in greater effect, sustainability and growth of the mission.